2007
DOI: 10.1152/ajprenal.00135.2007
|View full text |Cite
|
Sign up to set email alerts
|

Descending facilitation of spinal NMDA-dependent reflex potentiation from pontine tegmentum in rats

Abstract: This study was conducted to investigate whether dorsolateral pontine tegmentum stimulation modulates spinal reflex potentiation (SRP) and whether serotonergic neurotransmission is involved in such a modulation. Reflex activities of the external urethra sphincter (EUS) electromyogram in response to a test stimulation (TS; 1/30 Hz) or repetitive stimulation (RS; 1 Hz) on the pelvic afferent nerve in 35 anesthetized rats were recorded with/without synchronized train pontine stimulation (PS; 300 Hz, 30 ms) and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…The first attempt was to establish a stable baseline reflex activity and the RS-induced windup-like reflex potentiation (14,39,40). As shown in Fig.…”
Section: Baseline Reflex Activity and Windup-like Reflex Potentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first attempt was to establish a stable baseline reflex activity and the RS-induced windup-like reflex potentiation (14,39,40). As shown in Fig.…”
Section: Baseline Reflex Activity and Windup-like Reflex Potentiationmentioning
confidence: 99%
“…Next, we reexamined the role of glutamatergic neurotransmission in the induction of the RS-induced windup-like reflex potentiation (14,37,38,41). As shown in Fig.…”
Section: Glutamatergic Agonists and Antagonistsmentioning
confidence: 99%
“…Such in vivo preparations used in these studies maintained the whole neural network within the the central nervous system intact, thus offering an animal model to explore the possibility that activity-dependent reflex plasticity can be regulated by a specific nucleus that projects nerve fibers to the site where plasticity occurs. We recently explored the descending modulations on the reflex potentiation coming from the pontine reticular formation and reported that electric stimulation at the dorsolateral pontine tegmentum might activate the descending fiber to the spinal cord to facilitate SRP induction (11). In the present study, we further explored the possible neurotransmitter to activate this descending system by microinjecting nAChR agonists to the dorsolateral pontine tegmentum.…”
mentioning
confidence: 89%
“…The pelvic-urethra reflex, which is the reflexive closure of the urethra caused by bladder distension, is the neural basis for urine continence (15,16,17,22,35,36,48,49,50). Neurogenic hyperactivity and/or dyssynergia are believed to be participants in lower urinary tract dysfunctions, including interstitial cystitis (19,47).…”
mentioning
confidence: 99%